Prophylaxis for the Prevention of PJI after TAA: Is It Economically Justifiable?. Issue 4 (November 2022) - Martinazzi, Brandon J.; Kirchner, Gregory; Nam, Hannah; Dopke, Kelly; Mansfield, Kirsten N.; Ptasinski, Anna; Aynardi, Michael C.
Category: Ankle Arthritis; Ankle; Other Introduction/Purpose: Prosthetic joint infection (PJI) is a costly and potentially fatal complication in total ankle arthroplasty (TAA). Some surgeons will use intraoperative vancomycin powder or copiously irrigate the surgical site with Povidone-iodine to prevent this outcome. Additionally, many surgeons will prescribe a short course of postoperative antibiotics. However, the efficacy of such prophylaxis continues to be debated, and little is known about the cost-effectiveness of these agents. Therefore, the purpose of this study was to perform a 'break-even' analysis to determine the number of cases that could be performed while only preventing a single PJI and still breaking even on cost. Methods: The literature was searched to determine the rate of PJI and the mean cost of total ankle replacement. The prices of topical vancomycin powder and Povidone-iodine were obtained from our institution's purchasing records. An online drug database was then used to determine the cost of a 14 day twice daily course of Sulfamethoxazole/Trimethoprim (800/160 mg), Cephalexin (500 mg), and Amoxicillin/Potassium Clavulanate (875/125 mg). A break-even analysis was then performed to determine the absolute risk reduction (ARR) necessary to make a drug cost-effective. Using the ARR, we calculated the number of patients that would need to be treated with these agents to prevent a single PJI (NNT). Results: The price of intraoperative vancomycin powder was found to be $3.06 while povidone-iodine was found to cost $3.64. Sulfamethoxazole/Trimethoprim (800/160 mg), Cephalexin (500 mg), and Amoxicillin/Potassium Clavulanate (875/125 mg) were determined to cost $3.00, $3.64, and $14.51, respectively. At the prices obtained Vancomycin Powder, Povidone-iodine, Sulfamethoxazole/Trimethoprim, and Cephalexin were all cost-effective if the initial rate decreased by ARRs of 0.01%. Likewise, Amoxicillin/Potassium Clavulanate was cost-effective if the initial rate decreased by an ARR of 0.03%. Additional analyses run found that all drugs-maintained cost-effectiveness even if the initial rate of PJI was as low as 0.1%. Conclusion: PJI following TAA is devastating and costly. Despite the ongoing debate regarding the efficacy of prophylactic measures to reduce the risk of PJI in TAA, limited is known about their cost-effectiveness. Our study demonstrates that intraoperative vancomycin powder, povidone-iodine lavage, and multiple commonly prescribed antibiotics are all highly cost- effective to prevent PJI following TAA. We feel that a tailored approach to taking measures to reduce PJI with cost-effectiveness in mind is crucial to providing value-based care.